Action mechanism and molecular design of indolepyrrodione inhibitors targeting IDO1 - Wang, Xinmin; Zhang, Zhigang; Hu, Kaixuan; Yu, Wentong; Cheng, Yan; Song, Yuting; Sun, Xin; Li, Siyao; Yang, Tiantian; Hu, Jianping; Jing, Jing; Luo, Ting (Frontiers in Molecular Biosciences, 2025)
IntroductionThe incidence of cancer remains high, representing not only a major health threat to humanity but also a substantial economic burden to society. While conventional therapies include surgery, radiotherapy, and chemotherapy, immunotherapy—particularly immune checkpoint inhibitors (ICIs)—has emerged as a promising approach to enhance anti-tumor immunity. Indoleamine 2,3-dioxygenase 1 (IDO1), a cytoplasmic enzyme that regulates tryptophan catabolism, has become an important target for immunotherapeutic drug development.MethodsIn this study, a series of molecular simulation techniques were employed to investigate the molecular recognition and inhibition mechanisms between representative indolepyrrodione (IPD) inhibitor—specifically PF-06840003—and IDO1. Molecular dynamics simulations and structural analyses were conducted to characterize conformational changes of the IDO1 system. In addition, a 3D-QSAR study was performed on 26 IPD analogs using CoMFA and CoMSIA approaches to establish predictive structure–activity models.ResultsSimulation results revealed that the substrate/inhibitor access channel valve (JK-loop) in the IDO1_apo system adopts an open conformation, which transitions to a closed state upon binding of PF-06840003. The inhibitor forms multiple hydrogen bonds with residues in the active site, restricting JK-loop movement and consequently blocking the substrate L-Trp channel. This also narrows the O2/H2O molecular passage, reducing the efficiency of molecular entry and exit, and thereby attenuating the enzyme’s catalytic activity. The CoMFA and CoMSIA models exhibited high stability and strong predictive capability, providing reliable insights for further inhibitor optimization.DiscussionThese findings suggest a potential inhibitory mechanism for PF-06840003 and offer valuable structural insights for the rational design of potent IDO1 inhibitors. It should be noted that the inhibitory activity of the designed lead compounds is based solely on computational predictions; experimental validation through in vitro and in vivo studies is still required to confirm their actual inhibitory effects and pharmacokinetic properties.